Obesity and related health problems: An adult outpatient clinical setting [Genel dahi̇li̇ye poli̇kli̇ni̇ǧi̇ne başvuran hastalarda obezi̇te sikliǧi ve i̇li̇ş ki̇li̇ saǧlik problemleri̇] - (:unkn) unknown (My University, 2004)
Aim: To determine the frequency of obesity in an outpatient clinical setting and to assess the related health problems. Method: Among the 430 consecutive patients attending outpatient clinic, 399 subjects were recruited for final analysis. Fasting glucose, cholesterol, HDL, LDL, triglycerides levels were determined. All the subjects' blood pressure, waist and hip circumference, weight and height were measured and, body mass index(BMI) and waist/hip ratio (WHR) were calculated. Statistical analyses were performed using chi-square test, student-t test, Spearman's correlation analysis and odds ratio calculations. Results: 22.7%(n=89) of the total population were males, the average age was 50. The frequency of obesity was 31.6%. The percentages of underweight, normal, overweight, obese and morbid obese were 3.5%, 31.6%, 33.3%, 29.6%, and 2.0% respectively. Obesity seemed to be increasing progressively from the age of 40 and this increase seemed to be decreased slightly after the age of 60. WHR was the parameter which increased the odds ratio most for hypertension and hyperlipidemia (OR 3.2, 3.5 respectively), whereas BMI≥25 means two fold increased risk for diabetes (OR 1.9). Conclution: Approximately 1/3 of our outpatient subjects were classified as obese and/or morbidly obese. Therefore, physicians should not miss the chance of evaluating obesity status for all the patients.
Keywords: Body mass index; Obesity; Waist circumference; Waist/hip ratio